Pemberdayaan Kader Posyandu dalam Sosialisasi Kesehatan Reproduksi dan Mental pada Kalangan Remaja di Kelurahan Tongauna - Moita, Sulsalman; Sarpin; Damsid; Supiyah, Ratna; Rahman; Harjudin, Laode (CV. Literasi Indonesia, 2022)
Empowerment of Posyandu Cadres through the socialization of reproductive and mental health among adolescents aims to increase the capacity and skills of Posyandu Cadres in immunization services, community nutrition education, maternal and child health services, sex education for adolescents, and reproductive health counseling. To achieve this goal, the method used is training by focusing on the extension approach and FGD. The results show that the Empowerment of Posyandu Cadres through the socialization of reproductive and mental health among adolescents has the following functions: 1) increasing cadre capacity in the form of knowledge, experience, and technical skills in maternal and child health services, as well as knowledge of reproductive and mental health for adolescents; 2) Counseling on reproductive and mental health among adolescents will bring closer the understanding of Posyandu Cadres, parents, and government officials about the importance of instilling ethical and moral values ​​for youth; 3) The implementation of the discussion becomes a vehicle for exchanging information and experiences from the community service team, Posyandu cadres, midwives, and village officials; so that there is a shared commitment to socialize the movement for basic health services, to create cheap, healthy, fair and sustainable services.